2022
DOI: 10.1007/s00392-022-02024-z
|View full text |Cite
|
Sign up to set email alerts
|

Periprocedural myocardial injury according to optical characteristics of neointima and treatment modality of in-stent restenosis

Abstract: Aims Aim of the present study was to investigate the impact of increasing neointimal inhomogeneity and neoatherosclerosis as well as of treatment modality of in-stent restenosis (ISR) on the occurrence of periprocedural myocardial injury (PMI). Methods and results Patients with normal or stable/falling increased baseline high-sensitivity troponin T (hs-cTnT) undergoing intravascular optical coherence tomography (OCT) and subsequent percutaneous coronary in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…In a patient-level pooled analysis, the incidence of PMI based on the de nition according to the 4th universal de nition of myocardial infarction was 52.8% [5]. A retrospective study [11] investigated the effect of increasing neointimal heterogeneity and neoatherosclerosis on the incidence of PMI. Their results showed that the incidence of hs-cTnT-based PMI was approximately 30%, which was similar to our nding (37.9%).…”
Section: Disscusionmentioning
confidence: 99%
See 3 more Smart Citations
“…In a patient-level pooled analysis, the incidence of PMI based on the de nition according to the 4th universal de nition of myocardial infarction was 52.8% [5]. A retrospective study [11] investigated the effect of increasing neointimal heterogeneity and neoatherosclerosis on the incidence of PMI. Their results showed that the incidence of hs-cTnT-based PMI was approximately 30%, which was similar to our nding (37.9%).…”
Section: Disscusionmentioning
confidence: 99%
“…Studies on the association between neointimal characteristics and PMI occurrence after PCI for ISR has been extremely limited [11,20,21]. Lee et al [21] retrospectively analyzed the relationship between neointimal characteristics and the occurrence of PMI (de ned as creatine kinase-MB (CK-MB) > 99th percentile URL) in 125 patients with ISR lesions who underwent elective PCI and pre-PCI OCT examination.…”
Section: Disscusionmentioning
confidence: 99%
See 2 more Smart Citations
“…Repeated DES implantation is the most effective treatment for ISR ( Giacoppo et al, 2015 ; Siontis et al, 2015 ); however, interventional procedures are subject to complications such as perioperative myocardial injury (PMI) ( Nano et al, 2022 ). In addition to the reopening of diseased blood vessels, drug therapy for allergic inflammation is worthy of further study.…”
Section: Drug Therapiesmentioning
confidence: 99%